2019
DOI: 10.1111/cas.14119
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of patient‐derived organoids from a young patient with cervical clear cell carcinoma

Abstract: Cervical clear cell carcinoma (cCCC) constitutes an extremely rare subtype of cervical cancer. Consequently, its pathogenesis remains largely unknown, with no cell lines established from primary tumors. Here, we report the first establishment of cCCC organoids, from biopsy samples of a 23‐year‐old patient diagnosed with cCCC. By applying a protocol that we recently optimized for gynecological tumors, we were able to propagate a patient‐derived cell line (PDC) for more than 6 months as organoids. This PDC toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 49 publications
1
44
0
Order By: Relevance
“…However, there was little progress in their applicability to gynecologic tumors until recently [29], when we established an efficient culture method for ovarian and endometrial tumors [30], by modification of our Matrigel bilayer organoid culture (MBOC) protocol [31], which we previously developed for various murine cells. Moreover, for the first time, we established patient-derived organoids of cervical clear cell carcinoma, a rare type of cervical adenocarcinoma [32], further confirming the validity of the modified culture protocol for gynecologic tumors.In this study, we aimed to propagate normal cervical cells from the SCJ region by applying our modified MBOC protocol. We successfully expanded HPV-negative SCJ organoids, which were proved to retain many features of the SCJ.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…However, there was little progress in their applicability to gynecologic tumors until recently [29], when we established an efficient culture method for ovarian and endometrial tumors [30], by modification of our Matrigel bilayer organoid culture (MBOC) protocol [31], which we previously developed for various murine cells. Moreover, for the first time, we established patient-derived organoids of cervical clear cell carcinoma, a rare type of cervical adenocarcinoma [32], further confirming the validity of the modified culture protocol for gynecologic tumors.In this study, we aimed to propagate normal cervical cells from the SCJ region by applying our modified MBOC protocol. We successfully expanded HPV-negative SCJ organoids, which were proved to retain many features of the SCJ.…”
supporting
confidence: 63%
“…Such tissue samples were collected in a hospital immediately after surgery, and processed the next morning following overnight transfer to the lab while maintained in a cold media ( Figure 1A). As a culture media, we tested the standard culture media supplemented with EGF, R-spondin-1, Noggin, Jagged-1, and Rho-associated, coiled-coil containing protein kinase (ROCK) inhibitor Y27632, which we have confirmed robustly applicable to organoid culture of murine primary cells from various organs and human gynecological neoplasms [20,22,23,30,32], to facilitate future cross-referencing of organoids from various organs.…”
Section: Propagation Of Patient-derived Organoids From the Cervical Smentioning
confidence: 99%
“…Organoids were also obtained from cervical carcinoma biopsy tissue. Genomic analysis showed that the organoids contained several mutations, two of which were common with the tumor tissue, including nonsynonymous mutation in MLH1 and a synonymous mutation in TFE3 [ 93 ]. Organoid cultures of hepatocellular carcinoma and cholangiocarcinoma retained the histological architecture, gene expression and genomic landscape of the original tumor [ 91 ].…”
Section: Methods For Obtaining Spheroids and Organoidsmentioning
confidence: 99%
“…Patient-derived tumor organoids (PDTOs) not only recapitulate histological and genetic features of original tumors, but also allow high-throughput drug screening and potentially facilitate personalized therapy [13]. So far, long-term organoid cultures can be established from a variety of cancers, including colorectal [14], gastrointestinal [15], pancreas [16], liver [17], prostate [18], bladder [19], lung [20], and cervix [21] cancer etc. Breast cancer organoids have also emerged as a useful pre-clinical model for maintaining sufficient fidelity regarding the histology, transcriptome and genome [13].…”
Section: Introductionmentioning
confidence: 99%